A new method for the rapid detection of the antibacterial and bacteriostatic activity of disinfectants based on Propidium Monoazide combined with real-time PCR - Liu, Yanrong; Huang, Shuting; Zhou, Jungui; Zhang, Chi; Hu, Feijie; Xiao, Youyu; Qiu, Haopu; Yang, Yao (Frontiers in Microbiology, 2022)
Rapid detection of antibacterial and bacteriostatic properties is an important part of the quality and safety supervision of disinfectants. In this study, propidium monoazide (PMA) was used in combination with real-time PCR (PMA-qPCR) to detect the antibacterial and bacteriostatic activity of disinfectants against three commonly used indicator bacteria, Escherichia coli, Staphylococcus aureus, and Candida albicans, utilizing specifically designed primers. The method for preparing membrane-damaged bacteria was optimized to improve the ability of the PMA dye to distinguish between live and dead indicator bacteria. Finally, this method could simultaneously detect viable numbers of the indicator bacteria after the disinfectants were used. The R2 values of the PMA-qPCR standard curves were 0.9986, 0.9980, and 0.9962 for E. coli, S. aureus, and C. albicans, respectively, and the detection range was 103 106 CFU/ml, showing no significant difference in accuracy compared to that of the plate counting method (p > 0.05). The method established here is the first application of PMA-qPCR to detect the antibacterial and bacteriostatic activity of disinfectants. This technique markedly simplifies the detection steps of antibacterial and bacteriostatic activity, reduces the detection time (3 h compared to 48 72 h for the plate counting method), improves the quality supervision efficiency of disinfectants, and guarantees healthy and safe lives.